2016
DOI: 10.1152/advan.00121.2015
|View full text |Cite
|
Sign up to set email alerts
|

Value of artisanal simulators to train veterinary students in performing invasive ultrasound-guided procedures

Abstract: Pericardial effusion can lead to cardiac tamponade, which endangers an animal's life. Ultrasound-guided pericardiocentesis is used to remove abnormal liquid; however, it requires technical expertise. In veterinary medical education, the opportunity to teach this procedure to save lives during emergencies is rare; therefore, simulators are recommended for this practice. The present study aimed to create a model that can be made "at home" at low cost for ultrasound-guided pericardiocentesis training and to gathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 4 publications
(8 reference statements)
0
4
0
2
Order By: Relevance
“…Close-ended questions were answered using a visual analog scale system: the student specified the level of agreement with a statement by placing an X along a continuous 10-cm line between two end points. On each end-point of the scale, key words described the extreme values of the evaluated item (1,4). The words used were chosen to avoid misunderstandings, and an example question was provided to make the questionnaire easier to understand.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Close-ended questions were answered using a visual analog scale system: the student specified the level of agreement with a statement by placing an X along a continuous 10-cm line between two end points. On each end-point of the scale, key words described the extreme values of the evaluated item (1,4). The words used were chosen to avoid misunderstandings, and an example question was provided to make the questionnaire easier to understand.…”
Section: Methodsmentioning
confidence: 99%
“…Students described the model as realistic and reported that the experience prepared them to perform in vivo procedures. The authors mentioned that the participants could become familiar with the pericardiocentesis technique in a controlled and stress-free environment (4).…”
Section: Introductionmentioning
confidence: 99%
“…El desarrollo de experiencia técnica en procedimientos médicos es extremadamente importante para los profesionales del área de cuidados agudos y críticos, sin embargo, las oportunidades para ganar experiencia en el manejo de procedimientos críticos para salvar vidas en los cuidados de emergencias dependen de la oportunidad (Hage et al, 2016).…”
Section: Introductionunclassified
“…In an effort to diminish some of the associated cost with these models, there have been recent published reports on “home‐built” models that are not only constructed with readily available materials but also appear to be more cost‐effective. These models traditionally rely on the use of either gel wax‐ or gelatin‐based molds, which often require a minimum of several hours for the mold to be constructed …”
mentioning
confidence: 99%
“…These models traditionally rely on the use of either gel wax-or gelatinbased molds, which often require a minimum of several hours for the mold to be constructed. [13][14][15] We created a novel US-guided pericardiocentesis model that does not rely on a gel wax-or a gelatin-based mold for model preparation. The purpose of this study was to evaluate the feasibility of a novel, limited-use, low-cost pericardiocentesis model as a training tool for emergency physicians.…”
mentioning
confidence: 99%